Hubungan Karakteristik Demografi dan Psikografi Parabela dengan Peran Kepemimpinan dalam Melestarikan Hutan Kaombo - Husain, M. Najib; Haryadi, F. Trisakti; Wastutiningsih, Sri Peni (Program studi Penyluhan Pembangunan /Manajemen Pengembangan Masyarakat Pasca Sarjana Universitas Sebelas Maret Surakarta, 2016)
The purpose of this study was to analyze the relationship between demographic and psychographic characteristics of Parabela and leadership role in preserving Kaomboforest. The study used a combination of quantitative and qualitative methods (mixed method) by using survey approach (quantitative method) and an ethnographic approach (qualitative method). The results of Spearman's rho value of Parabela’s demographic characteristics such as age, occupation, land area, and number of dependant family showed no significant relationship. Only the education variable of parabela had a significant relationship with the leadership role in preserving KaomboForests. The correlation coefficient of education and leadership role, when referring to the interpretation guidelines, indicated that relationsip between the levels of education with leadership role in preserving Kaombo forests are in a very strong category. The psychographic relationship of Parabela and the leadership role suggested that economic motives, time motives and devotion motives had no significant relationship. There was a significant relationship between motif status and leadership role. The correlation coefficient of the relationship between motive status and leadership role, when referring to the guidelines for the interpretation of correlation,suggested that the motive of status and the leadership role in preserving the Kaombo forest is in a strong category. The result value of Spearman's rho of the relationship between demographic and psychographic characteristics of parabela with leadership role in conserving kaombo forests were in line with the real conditions, it is appeared as the parabela was formerly known as someone who is proactive in carrying out important roles as the sole ruler in Kadie prior to the present of any formal government. Parabela were now born as tge passive figure of traditional leaders and only present at situation when people are not able to ask for help from the village administration. Parabela still got the mandated role in society and also keep doing it, but the judgement from the society about the role were more because the society asked the parabela to carry out the role they have in preserving the Kaombo forest.